2009
DOI: 10.1097/sla.0b013e318193425a
|View full text |Cite
|
Sign up to set email alerts
|

Updated Systematic Review and Meta-Analysis of Randomized Clinical Trials on the Role of Mechanical Bowel Preparation Before Colorectal Surgery

Abstract: Although it did not confirm the harmful effect of mechanical bowel preparation (suggested by previous meta-analyses), this meta-analysis including almost 5000 patients, demonstrates with a high level of evidence that any kind of mechanical bowel preparation should be omitted before colonic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
150
5
18

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(179 citation statements)
references
References 23 publications
6
150
5
18
Order By: Relevance
“…54 With this in mind, Slim and colleagues published an updated meta-analysis and review of the literature which included 14 RCTs and nearly 5000 patients. 61 Although it did not confirm the harmful effect of MBP as previously suggested, it demonstrated that any kind of MBP can safely be omitted before colonic surgery.…”
Section: Role Of Mechanical Bowel Preparationmentioning
confidence: 42%
“…54 With this in mind, Slim and colleagues published an updated meta-analysis and review of the literature which included 14 RCTs and nearly 5000 patients. 61 Although it did not confirm the harmful effect of MBP as previously suggested, it demonstrated that any kind of MBP can safely be omitted before colonic surgery.…”
Section: Role Of Mechanical Bowel Preparationmentioning
confidence: 42%
“…Secondary endpoints examined complications inclusive of abscesses, wound infections, sepsis, reoperations and death. Results demonstrated no statistically signifi cant difference with respect to leak rates (p = 0.46), abdominal abscesses (p = 0.75), wound infections (p = 0.11), extra-abdominal sepsis (p = 0.12), reoperations (p = 0.63) or death (p = 0.70) [15]. The American Society of Colorectal Surgeons (ASCRS) support this by stating, "All types of mechanical preparation occasionally engender serious complications [16][17][18].…”
Section: Preoperative Bowel Preparationmentioning
confidence: 92%
“…No benefi t to MBP was seen and, in addition, several trials demonstrated increased morbidity with the use of MBP. In an updated 2009 metaanalysis, Slim et al examined 14 RCTs with a total of 4,859 patients undergoing colonic resection exclusively without inclusion of rectal cancer patients [15]. These patients were divided into two groups; 2,452 who had MBP and 2,407 who did not.…”
Section: Preoperative Bowel Preparationmentioning
confidence: 99%
“…anastomotic leakage, surgical-site infections etc.) In addition, there is a trend for increased complications for patients undergoing bowel preparation [45][46][47]. The largest metaanalysis, including almost 5,000 patients, demonstrated with a high level of evidence that all kinds of mechanical bowel preparation should be omitted before colonic surgery [46].…”
Section: (100% [Strong Consensus]; Gor C: 100% [Strong Consensus])mentioning
confidence: 99%